2020
DOI: 10.1111/1750-3841.15523
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of sugars, organic acids, phenolic compounds, antioxidant activity and the aroma fingerprint of small white apricots grown in Xinjiang

Abstract: Small white apricot is well known as a famous fresh fruit and even a folk medicine in Xinjiang. To investigate nutritive value, antioxidant activity, and flavor of small white apricot, sugars, organic acids, total flavonoids, phenolic compounds, antioxidant activities, and volatile compounds in five apricot cultivars were examined by high-performance liquid chromatography (HPLC) and headspace solid-phase microextraction coupled with gas chromatography-mass spectrometry (HS-SPME-GC-MS). The results showed that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(13 citation statements)
references
References 49 publications
1
9
0
Order By: Relevance
“…Finally, four alcohols, including Al4, Al5, Al6, and Al7, were the prominent aroma compounds measured in the samples belonging to Clusters 1 and 5, whereas they were the lowest metabolites detected in the samples included in Cluster 3. Alcohols mainly contribute to the flowery, green, and herbaceous odours in different fruits; consistent with early studies, they have previously been described as pertinent flavor volatiles in apricots (13,64). In line with the data reported in Table 2, we detected Al4, Al5, Al6, and Al7 in all of the apricot varieties belonging to Clusters 1 and 5.…”
Section: Volatile Compounds Analysissupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, four alcohols, including Al4, Al5, Al6, and Al7, were the prominent aroma compounds measured in the samples belonging to Clusters 1 and 5, whereas they were the lowest metabolites detected in the samples included in Cluster 3. Alcohols mainly contribute to the flowery, green, and herbaceous odours in different fruits; consistent with early studies, they have previously been described as pertinent flavor volatiles in apricots (13,64). In line with the data reported in Table 2, we detected Al4, Al5, Al6, and Al7 in all of the apricot varieties belonging to Clusters 1 and 5.…”
Section: Volatile Compounds Analysissupporting
confidence: 91%
“…Apricots contain many secondary metabolites, such as phenolic compounds (2), carotenoids (3)(4)(5)(6)(7), in particular β-carotene, and ascorbic acid (8)(9)(10). Also present in apricot are seed oils, which are essential for antioxidant activity, and, along with the pectin and mineral elements also contained in these fruits, they promote human health and affect fruit color and taste (11)(12)(13)(14). In addition to their functional ingredients, apricots and their derivatives are characterized by distinctive and alluring flavors, to which the presence of volatile compounds also contributes, favouring their consumption worldwide (15,16).…”
Section: Introductionmentioning
confidence: 99%
“…Standard references for sugars and organic acids were acquired from Sangon Biological Reagent Company (Shanghai, China). The extraction and analysis of sugars were performed based on a previous method [ 6 ]. The organic acids were determined using a previous method described by Chen et al [ 22 ] with some modifications.…”
Section: Methodsmentioning
confidence: 99%
“…Apricot output in Xinjiang reached 933,088,000 kg in 2018, and has become an important part of the income for local cultivators [ 5 ]. At present, apricots planted in Xinjiang include almost all the cultivars in China, but only a few species, such as Luopuhongdaike apricots, Xiaobai apricots and Semaiti apricots, are indigenous to the Xinjiang region [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Karatas and Sengul [49] reported sucrose as the main sugar in apricot cultivars in Turkey. Su et al [60] reported that in apricot fruits, sucrose was the main sugar, followed by glucose and fructose. Genard et al [61] reported the order of individual sugars in apricot fruits depending on their content was in descending order sucrose > glucose > fructose for all cultivars.…”
Section: Soluble Sugars and Sweetness Indicesmentioning
confidence: 99%